24.4k views
23 votes
Find the solution B=√2+√3-√2-√3

Find the solution B=√2+√3-√2-√3-example-1

2 Answers

14 votes
b= 0 because you take the square root of 2 + the square root of 3 and then subtract that by the square root of 2 and then subtract that by the square root of 3 it will give you zero
User Anton Serdyuk
by
5.1k points
11 votes

Answer:


B=√(2)

Explanation:

Original equation:


B = \sqrt{2+√(3)} - \sqrt{2 - √(3)}\\

Square both sides:


B^2=(\sqrt{2+√(3)})^2 + 2(\sqrt{2+√(3)} * (-\sqrt{2 - √(3)}) + (-\sqrt{2-√(3)})^2

Cancel out the square roots and squares:


B^2=2+√(3)}+ 2(\sqrt{2+√(3)} * (-\sqrt{2 - √(3)}) + 2-√(3)

Add the sqrt(3) and -sqrt(3) as well as 2 and 2


B^2=4 + 2(\sqrt{2+√(3)} * (-\sqrt{2 - √(3)})

Use the identity:
√(a) * √(b) = √(a * b) to rewrite the two square roots being multiplied:


B^2=4 + 2(-\sqrt{(2+√(3)) * (2 - √(3)}))

Use difference of squares:
(a-b)(a+b) = a^2-b^2


B^2=4 + 2(-\sqrt{2^2-√(3)^2})

Square both sides


B^2=4 + 2(-√(4-3))

Subtract:


B^2=4 + 2(-√(1))

Evaluate square root of 1:


B^2=4 + 2(-1)

Multiply


B^2=4 -2

Subtract


B^2=2

Take square root of both sides:


B=√(2)

User Ayatullah Rahmani
by
4.9k points